Predicting coronavirus anxiety based on resilience and self-concept in nurses - Mohammad Karamooz; Seyedeh Neda Amirnia; Fatemeh Sadat Mirkamali; ٍshrat Karimi Afshar (فصلنامه ابن سینا)
Background and aims: Fear of the unknown has always been a source of anxiety for human beings. With the outbreak of corona virus, anxiety has been observed in nurses, so monitoring its psychological consequences among them should be considered. The aim of this study was to predict the anxiety of the corona virus based on self-consept and resilience in the nurses. Methods: This analytical cross-sectional study was a correlational survey design. Among all nurses in the second half of 2020, 81 individuals were selected by simple random method. The participants responded to the questionnaires of self-concept (BSCT), resilience (CD-RIS), and anxiety of coronavirus (CDAS). Pearson’s correlation coefficient and regression were used to analyze the data. Results: The results showed that self-concept and resilience have the ability to predict the anxiety of the corona virus in nurses (p<0.001). Self-concept with a regression coefficient of  B = 0.203 and resilience with a value of B = 0.412 were able to directly predict the anxiety of coronavirus. Conclusion: Based on the results, the techniques of increasing self- consept and resilience can be used to reduce the anxiety of the coronavirus in nurses.